The Use of Predict Observe Explain and Write (POEW) Strategy to Improve Students’ Writing Achievement at Junior High School - Ach. Robi Barik Ramdhani (Faculty of Teacher Training and Education, 2025)
Writing is one of the most important skills in English learning because it enables students to express ideas and communicate meaning effectively. However, many junior high school students face difficulties in writing, especially in organizing ideas and applying correct writing conventions. A preliminary investigation with a seventh-grade English teacher in Jember showed that the students’ average writing score was 56.66, and none of them achieved the Minimum Mastery Criterion (KKM) of 75. This situation indicated that the students’ writing achievement needed to be improved. Therefore, this research aimed to improve the students’ writing achievement by implementing the Predict Observe Explain and Write (POEW) Strategy in teaching descriptive text writing. This study applied a Classroom Action Research (CAR) design adapted from Kemmis and McTaggart (1988), which consists of four stages: planning, action, observation, and reflection. The research was conducted at a junior high school in Jember, East Java, involving 32 seventh-grade students in the 2025 academic year. The data were collected using a writing test and an observation checklist. The writing test was used to measure the students’ writing achievement, while the observation checklist was used to record the students’ active participation during the implementation of POEW Strategy. Based on the data obtained, the implementation of POEW Strategy improved the students’ writing achievement. The mean score of the writing post test improved from the baseline data, which was 56.66, to 78.13. Moreover, 25 out of 32 students (78.13%) achieved a score of 75 or higher, meeting the KKM. The observation results also showed that the students’ active participation improved,
My dedicated supervisor : Dra. Zakiyah Tasnim, M.A.,
Keywords: Prediction; Observe; Explain; Write; POEW